Comparative Efficacy of different Funnel Diameters in Light Traps against Major Phototactic Insect Pests of rabi Season - Patil, Rameshwar; Sharma , Amit Kumar; Das , S. B.; Kumar , Neeraj; Choudhary , Priyal; Patel , Dhruv Kumar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Light traps have been long used to reduce and manage insect populations. Although there are numerous types and designs of insect light traps. Four distinct light traps were employed for the study and positioned within the BSP Unit Adhartal, JNKVV Jabalpur from mid-November 2022 to mid-April 2023 for the study of the efficiency test of different funnel diameters of light traps based on performance. Comparative studies of light trap catches revealed that 50 cm funnel diameter light traps have given higher response in following species for Helicoverpa armigera (13.91%), Agrotis ipsilon (14.36%), Creatonotus gengis (13.97%), Gryllus bamaculatus (22.26%), Gryllotalpa orientalis (45.30%), Nezara viridula (9.82%), Amata cyssea (13.35%), Asota ficus (7.01%), Perina nuda (21.78%), and Thysanoplusia orichalcea (22.75%). There was a statistically significant increase in trap catches in the 50 cm funnel diameter light traps compared to the 40 cm funnel diameter traps. However, there was a statistically non-significant difference between the 40 cm and 50 cm funnel diameter traps for Spodoptera litura and Theretra oldenlandiae species, although the trap catches were numerically higher in the 50 cm funnel diameter traps because 50 cm funnel diameter provide large catchment area for insects.